Summabilty of the Fourier-Laplace series in the Nikol’skii spaces - Rakhimov, Abdumalik (AIP Publishing, 2023)
In this paper we study convergence and summability problems of the series associated with the Laplace-Beltrami operator on the unique sphere. These series known as Fourier-Laplace series and we study the behaviour of these series in the different spaces of smooth functions with respect number of topologies.